Experience with the evidence map in oral ozone therapy - importance for integrative and complementary health practices (Research, Society and Development, 2021)
medical and dental treatment in the form of ozonized water and oxygen / ozone gas mixture and associated with photobiomodulation therapy. The evidence map was based on the 3iE evidence searched in the databases: LILACS, PubMed, EMBASE and Cochrane Library, seeking systematic and narrative reviews, analyzed in an excel characterization spreadsheet. Three independent literature reviewers screened the systematic review search output blinded at the software Rayyan. The full-text publications were screened against the specified inclusion criteria by thre independent reviewers; disagreements were resolved through discussion. Forty-two studies were found, 16 of which were systematic reviews and 26 narrative reviews, published between 2006 and 2021, with different levels of confidence. The intervention that most appeared in the literature was oral ozone therapy as a bacterial colony reduction and decontamination agent, with emphasis on topical oxygen-ozone gas mixtures, topical ozonized water. Oral ozone therapy can bring benefits to clinical practice and patients. The evidence map provides an easy visualization of valuable information for patients, health practitioners and managers, in order to promote evidence-based complementary therapies.